2009
DOI: 10.1016/j.mce.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Injury-induced mineralocorticoid receptor expression involves differential promoter usage: A novel role for the rat MRβ variant

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Neuronal injury results in increased mineralocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In rat MR, three distinct mRNA transcripts differing at the 5=UTR but encoding the same protein have been observed (30). Furthermore, deletion of 10 bp, resulting in truncation of the LBD in rat MR and differential expression of rat transcript variants in response to neuronal stress, have been also reported (27,67). Moreover, mammalian mRNA isoforms of MR show tissue-related expression (46,59,67).…”
Section: Discussionmentioning
confidence: 97%
“…In rat MR, three distinct mRNA transcripts differing at the 5=UTR but encoding the same protein have been observed (30). Furthermore, deletion of 10 bp, resulting in truncation of the LBD in rat MR and differential expression of rat transcript variants in response to neuronal stress, have been also reported (27,67). Moreover, mammalian mRNA isoforms of MR show tissue-related expression (46,59,67).…”
Section: Discussionmentioning
confidence: 97%
“…30, 31, 32, 33, 34, 35 Context-dependent changes in MR expression can be established by distinct 5′ MR mRNA transcripts (MRα and MRβ), each having its own promoter containing regulatory elements and showing differential expression depending on tissue, time and availability of steroids and stress. 6, 30, 36, 37, 38 SNPs may result in differential expression of MRα vs MRβ by affecting TF binding or splicing. Two of the eight common 5′ UTR SNPs were consistently predicted to influence TF binding while a third SNP was predicted to affect a glucocorticoid responsive element-consensus sequence (although not consistent).…”
Section: Discussionmentioning
confidence: 99%
“…differences amongst groups in the expression of a particular splice variant will be more pronounced. It has been shown that their expression in cellular stress in a primary culture of cortex cells varies irregularly (Kang et al, 2009). Here we analyze only the total pool of NR3C2 mRNA, because the fox genome had not been annotated in sufficient detail.…”
mentioning
confidence: 99%